2002
DOI: 10.1002/ca.10057
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous flexor of the little finger

Abstract: We report an anomalous palmar muscle belly of the flexor digitorum superficialis muscle (FDS) in the right hand of an 80-year-old female cadaver. The muscle originated from the center of the volar surface of the flexor retinaculum and inserted onto the palmar aspect of the base of the middle phalanx of the little finger. Its tendon of insertion divided into two bands, a pattern typical of the FDS tendon, between which the tendon of flexor digitorum profundus muscle to the little finger passed. The tendon of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…While the incidence of additional tendon / muscle slips were not assessed in our cadaveric study, the incidence of accessory muscle bellies or heads was found to be substantially lower at 0.16% of forearms or 0.32% of individuals, mirroring the rare reporting of true accessory muscles in reported studies. These studies comprise accessory muscles of the FDS, FDP, and FPL (Still and Kleinert, 1973;Lahey and Aulicino, 1986;Schon et al, 1992;Steinberg and Szabo, 1996;Wahba et al, 1998;Elliot et al, 1999;Koizumi et al, 2002;Kobayashi et al, 2003;Lindley and Kleinert, 2003;Barbe et al, 2005). In these studies, the variations in muscle location, attachments and structure have been variably associated with variations in local vasculature and innervation, and furthermore have been associated with clinical sequelae including compression neuropathies and iatrogenic injury.…”
Section: Discussionmentioning
confidence: 96%
“…While the incidence of additional tendon / muscle slips were not assessed in our cadaveric study, the incidence of accessory muscle bellies or heads was found to be substantially lower at 0.16% of forearms or 0.32% of individuals, mirroring the rare reporting of true accessory muscles in reported studies. These studies comprise accessory muscles of the FDS, FDP, and FPL (Still and Kleinert, 1973;Lahey and Aulicino, 1986;Schon et al, 1992;Steinberg and Szabo, 1996;Wahba et al, 1998;Elliot et al, 1999;Koizumi et al, 2002;Kobayashi et al, 2003;Lindley and Kleinert, 2003;Barbe et al, 2005). In these studies, the variations in muscle location, attachments and structure have been variably associated with variations in local vasculature and innervation, and furthermore have been associated with clinical sequelae including compression neuropathies and iatrogenic injury.…”
Section: Discussionmentioning
confidence: 96%
“…This muscle starts from the forearm and it inserts onto the radial and ulnar aspects of the proximal half of the middle phalanx of the fifth finger when it is present and is enervated by the median nerve(2). This muscle has been shown to be absent in 2% of the Japanese population(3), and others have reported its absence to be 6% (bilateral) and 6.8% (unilateral)(4). Contradictory hypotheses for the development of the FDS muscle belly(3) have been proposed, single origin (either antebrachial or palmar) and dual origin (both antebrachial and palmar).…”
Section: Discussionmentioning
confidence: 99%
“…This muscle has been shown to be absent in 2% of the Japanese population(3), and others have reported its absence to be 6% (bilateral) and 6.8% (unilateral)(4). Contradictory hypotheses for the development of the FDS muscle belly(3) have been proposed, single origin (either antebrachial or palmar) and dual origin (both antebrachial and palmar). Kobayashi et al referred to Yamada's supposition that the FDS muscle originates first in the palm and then migrates to the forearm(3) due to the results of their study as well as another reporting “brevis-type” variations of the FDS to the finger in question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver showed macroscopical alterations corresponding to cirrhosis. The cadaver was voluntarily donated to the Ehime University and processed for fixation and disinfection as previously reported (Kobayashi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%